The selection and identification of compound housekeeping genes for quantitative real‐time polymerase chain reaction analysis in rat fetal kidney. Issue 3 (10th August 2021) - Zhao, Xiaoqi; Chen, Haiyun; Zhu, Yanan; Liu, Yi; Gao, Lili; Wang, Hui; Ao, Ying
Abstract: During quantitative real‐time polymerase chain reaction (RT‐qPCR) data analysis, the selection of optimal housekeeping gene is necessary to ensure the accuracy of results. It is noteworthy that housekeeping genes commonly used in adult studies may not be applicable for fetus. However, the stability analysis of housekeeping gene in fetal kidney has not been reported. This study intends to screen the applicable compound housekeeping genes in rat fetal kidney. In this study, eight housekeeping genes used in kidney studies based on literature reports ( GAPDH, ACTB, 18S, HPRT, YWHAZ, HMBS, PPIA, and TBP ) were selected as the research object. Their expression levels in the rat fetal kidney in physiological condition and the intrauterine growth retardation (IUGR) model induced by prenatal dexamethasone exposure (PDE) (0.2 mg/kg·day from gestation Days 9 to 20) was measured. Furthermore, these eight housekeeping genes were used to conduct relative quantitative analysis of nephrin expression in the fetal kidney in PDE‐induced IUGR model, to compare the influence of choosing different housekeeping gene on data analysis of nephrin expression and to verify the reliability of selected compound housekeeping genes. In this study, stable housekeeping genes of fetal kidney tissues in PDE‐induced IUGR model were identified: ACTB, GAPDH, TBP, and HMBS for males; ACTB, YWHAZ, and GAPDH for females. Besides, our results suggest that ACTB  +  GAPDH were the best compound housekeeping genes for normalization analysis in male fetal kidney studies, and ACTB  + Y WHAZ in females. This study will provide an experimental evidence basis for the selection of housekeeping genes in the RT‐qPCR experiment in renal development toxicology‐related models. Abstract : This study screened and determined the applicable compound housekeeping genes in rat fetal kidney in the physiological condition and prenatal dexamethasone exposure (PDE)‐induced IUGR model. Our results suggest that in the PDE‐induced IUGR model, ACTB  +  GAPDH were the best compound housekeeping genes for normalization analysis in male fetal kidney studies, and ACTB  + YWHAZ in females.